Design of the KIMIMIX Learning Management System as a future practicum innovation - Muhamad Firmansya Junus; Asna Istikmalatul Muktamaroh; Henry Praherdhiono; Yerry Soepriyanto (Inovasi Kurikulum)
Innovation in chemistry laboratories can be integrated with the help of a Learning Management System (LMS). This innovation allows educators to provide video content, modules, and auxiliary tools to enhance students' performance in conducting experiments in the laboratory. This research aims to develop a Moodle-based KIMIMIX Learning Management System Design that adapts the Outcome Based Education (OBE) theory, developed by the skills needed by chemistry students who will be oriented toward future practical innovation. This research and development method adapts the ADDIE model at the Analysis and Design stage. The research sample comprised 24 students taking the first semester of the Chemistry study program at Gorontalo State University. The research process is a preliminary study, needs analysis, material analysis, media analysis, and media innovation analysis with data collection techniques using an open-ended questionnaire given to 114 students. The results of the design stage include media specifications (media formats, text fronts, grammar, themes, supporting software), flowcharts, and design implementation. The KIMIMIX LMS research design as a future practicum innovation is declared ready to implement the design at the product development stage. The detailed design is hoped to produce a sophisticated LMS product for chemical practicums.